ISOSPECTRALITY PROBLEM FOR DIRAC SYSTEM - Panakhov, Etibar S.; Gulsen, Tuba (Inst Mathematics & Mechanics, Natl Acad Sciences Azerbaijan, 2014)
In this paper, we investigate the isospectrality problem for Dirac system by using Gelfand-Levitan integral equation and transmutation operators.
Keywords: Dirac system; isospectrality problem; Gelfand-Levitan integral equation; transmutation operator